PLANTS AND HUMAN HISTORY - Maheshwari, P. (SCHOOL SCIENCE, 2013)
There is often an impression in the mind of the layman that the study of botany is an innocent pastime peculiarly suited to the female sex because of the nice colours, elegance, and fragrance of flowers and plant parts. They do not soil their nice dresses, nor give out the foul smells characteristic of a laboratory dealing with animals. There is also not much danger of burning the hands, or of having to exert the brain with difficult mathematical problems as in physics and chemistry. All of these premises are false as botanists will no doubt appreciate and understand at once. As I shall try to show, for obtaining plants men have gone forth with the sword to distant lands, set upon long voyages of discovery, and conquered new lands. In fact, even in the modern world, plant power means as much or more than water power, sea power, atomic energy, and so on.